Modelling the effects of user learning on forced innovation diffusion - Zhang, Tao; Siebers, Peer-Olaf; Aickelin, Uwe (2012)
Technology adoption theories assume that users’ acceptance of an innovative technology is on a voluntary basis. However, sometimes users are force to accept an innovation. In this case users have to learn what it is useful for and how to use it. This learning process will enable users to transit from zero knowledge about the innovation to making the best use of it. So far the effects of user learning on technology adoption have received little research attention. In this paper - for the first time - we investigate the effects of user learning on forced innovation adoption by using an agent-based simulation approach using the case of forced smart metering deployments in the city of Leeds.